An Overview of Ergonomics Problems Related to CNC Machining Operations - Isa , Halim; Syed Mohamed, Muhammad Syafiq (2013)
In the new era of advanced manufacturing technology, machine tool design plays an important role in maximizing productivity and occupational health of industrial workers. However, the machine tool manufacturers face difficulty in designing an ergonomic machine tool that can be suited to Malaysian industrial workers because almost all machine tools were designed according to physical dimensions, capabilities and limitations of European or American populations. This mismatch between machine design and worker abilities may eventually lead to occupational injuries. Therefore, the purpose of this paper is to disseminate information on ergonomics problem,assessment methods, and control measures associated with CNC machining operation. Published articles related to CNC machining operation have been reviewed. Based on published researches,work-related musculoskeletal disorders such as low-back pain, neck and shoulder problem have been identified as common health problems associated with the machine operation. Engineering and administrative controls have been proposed to minimize the health problems.